Data driven e-science use cases andsSuccessful applications of distributed computing infrastructures (ISGC 2010) - International Symposium on Grid Computing (2010 Taipei, Taiwan); Lin, Simon C.; Yen, Eric.; SpringerLink (Online service). (New York Springer, 2011)
GC 2010, The International Symposium on Grid Computing was held at Academia Sinica, Taipei, Taiwan, March, 2010. The 2010 symposium brought together prestigious scientists and engineers worldwide to exchange ideas, present challenges/solutions and to discuss new topics in the field of Grid Computing. Data Driven e-Science: Use Cases and Successful Applications of Distributed Computing Infrastructures (ISGC 2010), an edited volume, introduces the latest achievements in grid technology for Biomedicine Life Sciences, Middleware, Security, Networking, Digital Library, Cloud Computing and more. This book provides Grid developers and end users with invaluable information for developing grid technology and applications. The last section of this book presents future development in the field of Grid Computing. This book is designed for a professional audience composed of grid users, developers and researchers working in the field of grid computing. Advanced-level students focused on computer science and engineering will also find this book valuable as a reference or secondary text book.
Part I Asia Federation Report -- Asia Federation Report on International Symposium on Grid Computing (ISGC) 2010 -- Part II Keynote Speech -- Roadmap for the Uptake of the e-Infrastructure in the Asia-Pacific Region -- Part III Grid Activities in Asia Pacific -- Uptakes of e-Science in Asia -- EU-IndiaGrid2 Sustainable e-Infrastructures across Europe and India -- Pathway to Support the Sustainable National Health Information System -- Part IV Grid Security and Networking -- TERENA eScience PKI -- Part V Grid Operation and Management -- SEE-GRID eInfrastructure for Regional eScience -- Peer-to-peer Cooperative Scheduling Architecture for National Grid Infrastructure -- The EUAsiaGrid Roadmap: Paths to a Sustainable, Persistent e-Infrastructure in the Asia-Pacific Region -- From EGEE Operations Portal towards EGI Operations Portal -- Kolkata Tier-2 Centre: Administration and Installation -- Performance Analysis of EGEE-like Grids in Asia and Latin America -- GOCDB4, a New Architecture for the European Grid Infrastructure -- An APEL Tool Based CPU Usage Accounting Infrastructure for Large Scale Computing Grids -- HLRmon, a Tool for Advanced Visualization of Resource Utilization -- Part VI Grid Middleware and Interoperability -- Interoperating AliEn and ARC for a Distributed Tier1 in the Nordic Countries -- Toward SVOPME, a Scalable Virtual Organization Privileges Management Environment -- The D4Science Approach toward Grid Resource Sharing: The Species Occurrence Maps Generation Case -- An Efficient Grid Data Access with StoRM -- Design and Implementation of a Multi-Grid Resource Broker for Grid Computing -- Part VII Digital Library and Content Management -- The Quality in Quantity - Enhancing Text-based Research -- Grid Application Meta-Repository System: Repository Interconnectivity and Cross-domain Application Usage in Distributed Computing Environments -- Part VIII Grid Computing and Cloud Computing -- Integration of Cloud and Grid Middleware at D-Grid Resource Center Ruhr -- Distributed Parametric Optimization with the Geneva Library -- Determining Overhead, Variance & Isolation Metrics in Virtualization for IaaS Cloud -- Analyzing the Applicability of Airline Booking Systems for Cloud Computing Offerings -- Part IX Applications on High Energy Physics -- E-infrastructure for FAIR -- Grid Computing Operations for the CMS Experiment at the GRIF Tier-2 -- From the CMS Computing Experience in the WLCG STEP?09 Challenge to the First Data Taking of the LHC Era -- First Experiences with CMS Data Storage on the GEMSS System at the INFN-CNAF Tier-1 -- Part X Applications on Humanities and Social Sciences -- GENESIS Social Simulation -- Part XI Applications on Earth Sciences and Mitigation -- A Grid Application on Climate Change in EUAsiaGrid -- Lessons Learned in Thailand from 2004 Tsunami -- Efficient Bulk Data Replication for the EarthSystem Grid -- Grid Computing for Disaster Mitigation -- Part XII Applications on Biomedicine and Life Sciences -- Applicability of Free Energy Calculations Using High?Throughput Grid Approach -- Grid Computing for Bioinformatics: An Implementation of a User-Friendly Web Portal for ASTI's In Silico Laboratory -- Grid Computing Technology and the Recurrence Quantification Analysis to Predict Seizure Occurrence in Patients Affected by Drug-Resistant Epilepsy -- Construction of the Platform for Phylogenetic Analysis.
Electronic reproduction.
Keywords: Computational grids (Computer systems) -- Congresses; Electronic data processing -- Distributed processing -- Congresses; Electronic books